Analisis Regresi Logistik pada Karakteristik Perempuan Berumur 15-49 Tahun yang Tidak Pernah Menggunakan Alat Kontrasepsi (KB) di Kabupaten Bintan - Dio Dwi Saputra (Politeknik Statistika STIS, 2022)
The Family Planning Program (KB) held by the Indonesian government has different levels of achievement between regions. Bintan Regency is the regency with the highest percentage of ever-married women aged 15-49 years who have never used contraception in the Riau Islands Province. So, this study aims to determine the characteristics of women aged 15-49 years and their effects. The inferential analysis method used is binary logistik regression analysis. The findings of this study are women aged 15-49 years in Bintan Regency whose age at first marriage is 21 years and over, have a senior high school/equivalent education and college education, does not work, does not use the internet and does not have health insurance, has a tendency not to use contraception. Meanwhile, women who live in rural areas, have a junior high school/equivalent education and are in non-poor households tend to use contraception. The government must optimize the socialization of the family planning program and make policies, which have a direct or indirect impact on women’s decisions to participate in the family planning program.